Os limites do lulismo: liderança política e racionalidade governam - França, Leonardo Bueno (2016)
This paper brings together arguments and statistics data collected about the limits of the stated governability pattern reaffirmed by the government management of Lula and Dilma Rousseff. Guided by reference to the term "lulism" embracing its content through a historical and institutional perspective, it draws the conclusion that the political leadership profile forged by a symbiotic process between the Workers' Party (PT) and the State resized the odds of influence on the political system, the governance practices and its selectivity strategies. Understanding lulism as a governability pattern producer of governance capacity in order to reconcile the class-conflicts within the public administration, in addition to the PT institutionalization process and the consequent redesign of its leadership profile and support base, the pattern proved itself unsustainable with the addition of some variables. Stands out: the macroeconomic shrinking; the growing party fragmentation; the leadership deficit, the rapid growth of the most conservative bloc in the legislature since 1964 and the dysfunctions and internal differences of the two main coalition parties, PT and PMDB